Svalbarðs fundr: The Place Name Svalbard and Its Connotations in Medieval and Modern Literature and Cartography - Chekin, Leonid S. (Nordlit, 2020)
The paper analyses medieval forms of the name Svalbard as applied to the land “discovered” in 1194, suggests that this Arctic discovery could have been named after a farmstead in Iceland, and follows the story of the name by discussing its contexts in medieval and modern literature and on maps. However little information about Svalbard survived in the Icelandic annals, the Landnámabók, and related texts, it became part of competing visions of the Arctic, from the late medieval Samsons saga fagrathrough the adoption of Svalbard as the name of a new territory under Norwegian rule in 1925.